“Prion-like” seeding and propagation of oligomeric protein assemblies in neurodegenerative disorders - Zampar, Silvia; Di Gregorio, Sonja E.; Grimmer, Gustavo; Watts, Joel C.; Ingelsson, Martin (Frontiers in Neuroscience, 2024)
Intra-or extracellular aggregates of proteins are central pathogenic features in most neurodegenerative disorders. The accumulation of such proteins in diseased brains is believed to be the end-stage of a stepwise aggregation of misfolded monomers to insoluble cross-β fibrils via a series of differently sized soluble oligomers/protofibrils. Several studies have shown how α-synuclein, amyloid-β, tau and other amyloidogenic proteins can act as nucleating particles and thereby share properties with misfolded forms, or strains, of the prion protein. Although the roles of different protein assemblies in the respective aggregation cascades remain unclear, oligomers/protofibrils are considered key pathogenic species. Numerous observations have demonstrated their neurotoxic effects and a growing number of studies have indicated that they also possess seeding properties, enabling their propagation within cellular networks in the nervous system. The seeding behavior of the oligomers differs between the proteins and is also affected by various factors, such as size, shape and epitope presentation. Here, we are providing an overview of the current state of knowledge with respect to this "prion-like" behavior of soluble oligomers for several of the amyloidogenic proteins involved in neurodegenerative diseases. In addition to providing new insight into pathogenic mechanisms, research in this field is leading to novel diagnostic and therapeutic opportunities for neurodegenerative diseases.